Effective interventions for social-emotional learning - Gresham, Frank M. (The Guilford Press, 2018)
"This book reviews evidence-based, multi-tiered practices for promoting social-emotional learning (SEL) with typically developing students as well as those with special needs. Leading authority Frank M. Gresham, codeveloper of the Social Skills Improvement System Rating Scales, describes how to systematically assess K-12 students' social skills and plan and implement universal, selected, and intensive interventions. His approach is grounded in cutting-edge research on social-emotional competencies and their role in adjustment and academic achievement. Emphasizing what works, the book showcases programs and strategies that are sequenced, active, focused, and explicit. Detailed case examples and lesson plans illustrate different levels and types of SEL intervention. Reproducible assessment tools can be downloaded and printed in a convenient 8 1/2" x 11" size. Subject Areas/Key Words: academic achievement, adolescents, assessments, behavioral disorders, children, classrooms, competence, curricula, deficits, emotional intelligence, evidence-based interventions, mental health, MTSS, multitiered systems of support, PBIS, peer relationships, positive behavior interventions and supports, positive behavior supports, programs, response to intervention, RTI, school consultation, school psychology, screening, SEL, social behavior, social development, social-emotional learning, Social Skills Improvement System Rating Scales, social skills training, special education, teaching Audience: School psychologists, behavioral specialists, child clinical psychologists, and school social workers working with children ages 5-17 (grades K-12), who will use the book in collaboration with teachers and special educators; also of interest to school administrators"--